QSAR of a Group of Sulphonamides as Carbonic Anhydrase Inhibitor I - Sharma, Saumya (International Journal of Pharmaceutical & Biological Archive, 2012)
QSAR of a Group of Sulphonamides as Carbonic Anhydrase Inhibitor I